Consensus nomenclature for CD8(+) T cell phenotypes in cancer - Apetoh, Lionel; Smyth, Mark J.; Drake, Charles G.; Abastado, Jean-Pierre; Apte, Ron N.; Ayyoub, Maha; Blay, Jean-Yves; Bonneville, Marc; Butterfield, Lisa H.; Caignard, Anne; Castelli, Chiara; Cavallo, Federica; et al. (OncoImmunology, 2015)
Whereas preclinical investigations and clinical studies have established that CD8(+) T cells can profoundly affect cancer progression, the underlying mechanisms are still elusive. Challenging the prevalent view that the beneficial effect of CD8(+) T cells in cancer is solely attributable to their cytotoxic activity, several reports have indicated that the ability of CD8(+) T cells to promote tumor regression is dependent on their cytokine secretion profile and their ability to self-renew. Evidence has also shown that the tumor microenvironment can disarm CD8(+) T cell immunity, leading to the emergence of dysfunctional CD8(+) T cells. The existence of different types of CD8(+) T cells in cancer calls for a more precise definition of the CD8(+) T cell immune phenotypes in cancer and the abandonment of the generic terms "pro-tumor" and "antitumor." Based on recent studies investigating the functions of CD8(+) T cells in cancer, we here propose some guidelines to precisely define the functional states of CD8(+) T cells in cancer.
EVALuna2:19573